Nanoscale model catalysts supported by metal organic frameworks - Young, Cyril (University of the Free State, 2009)
The aim of this study was to use square planar platinum(II) and palladium(II) complexes for the synthesis of bridged complexes and as building blocks for the subsequent construction of two dimensional metal organic frameworks. For this purpose, pyrazine, 2,2‟ -bipyrimidine (bpym) and 4,4‟-bipyridine (4,4-bipy) were chosen as rigid bridging ligands. 4,5-Diazafluoren-9-one (Daf) was used as a non-bridging ligand in some of the investigations. The optimum conditions for crystallization of these bridged species were determined in order to co-crystallize the complexes with synthesized crystalline inorganic supports, which consisted of titanium and tungsten oxide. Characterization of the complexes was done by Infrared spectroscopy and Nuclear Magnetic Resonance spectroscopy (NMR). Single crystal X-ray crystallographic structure determinations of the following compounds were completed: cis-[Pd(PPh3)2(Daf)2].-(Trif)2.CH3NO2, cis- [Pd2BpymCl4].DMF and cis-[Pd(PPh3)2(NO3)2].CO(CH3)2 . cis-[Pd(PPh3)2(Daf)2].(Trif)2.CH3NO2 crystallized in the monoclinic space group P2/n with Z =4 in a unit cell with dimensions: a = 15.184(1) Å, b = 17.112(1) Å, c = 22.256(2) Å, α = 90 °, β = 99.676(4) °, γ = 90 ° at 100 K. Least-squares refinement led to a value of the conventional R index of 0.0750 and Rw = 0.1930 for 12345 reflections having I > 2σ(I). The palladium ion is coordinated cis with two phosphorus and two nitrogen atoms. The formal geometry of the palladium center is square planar. In addition there is an interaction between uncoordinated nitrogen atoms of 4,5-diazafluoren-9-one ligand in the axial positions, which results in the formation of a pseudo octahedral structure. A 50% disorder is present on one of the phenyl rings and one of the triflate counter ions. The Rw value is high as the result of one carbon atom and its hydrogen atoms not being located on the disordered acetone solvate. cis-[Pd2BpymCl4].DMF crystallized in the monoclinic space group C2/m with Z = 2 in a unit cell with dimensions: a = 10.73(7) Å, b = 14.24(8) Å, c = 5.938(2) Å, α = 90 °, β = 108.229(4) °, γ = 90 ° at 100 K. Least-squares refinement led to a value of the conventional R index of 0.032 and Rw = 0.0893 for 1110 reflections having I > 2σ(I). The complex consists of two palladium centers linked by the 2,2‟-bipyrimidine ligand. Each palladium atom is coordinated by two chlorido ions, two nitrogen atoms and has a square planar geometry. A 25 % disorder is found on the DMF solvate. cis-[Pd(PPh3)2(NO3)2].CO(CH3)2 crystallized in the monoclinic space group C2/c with Z = 4 in a unit cell with dimensions: a = 40.343(2) Å, b = 9.749(1) Å, c = 19.78(1) Å, α = 90 °, β = 115.514(1) °, γ = 90 ° at 100 K. Least-squares refinement led to a value of the conventional R index of 0.0773 and Rw = 0.1873 for 8638 reflections having I > 2σ(I). The complex consists of a square planar geometry at the palladium center coordinated to two oxygen atoms and two phosphorus atoms in a cis fashion. The high Rw value is a result of one carbon and its hydrogen atoms not being located on the disordered acetone solvate. A preliminary catalytic investigation was attempted using cis-[Pd2BpymCl4].DMF in Heck coupling and the Wacker oxidation process. However, no reproducible results were obtained due to infrastructural and time constraints.

Die doel van hierdie studie was om vierkantig-planêre platinum(II) en palladium(II) brugkomplekse te sintetiseer en as boustene vir die daaropvolgende konstruksie-boustene vir tweedimensionele organometaalraamwerke te gebruik. Die starre vlakligande pyrasien, 2,2‟- bipirimidien en 4,4‟-bipiridien is vir hierdie doel gekies. 4,5-diazafluoren-9-one (Daf) is gebruik as „n nie brugende ligand. Die optimum kondisies vir die kristallisasie van hierdie gebrugde spesies is bepaal om dit in opvolgende stappe met gesintetiseerde kristallyne anorganiese titaan- en wolframgebaseerde vaste steunraamwerke, te ko-kristalliseer. Die komplekse is met behulp van Infrarooi- (IR) en kernmagnetiese resonansspektroskopie (KMR) gekarakteriseer. Suksesvolle enkelkristal X-straalkristallografiese struktuurbepalings is van die volgende verbindings gedoen: cis-[Pd(PPh3)2(Daf)2].(Trif)2.CH3NO2, cis- [Pd2BpymCl4].DMF en cis-[Pd(PPh3)2(NO3)2].CO(CH3)2 . cis-[Pd(PPh3)2(Daf)2].(Trif)2.CH3NO2 kristalliseer in die monokliniese ruimtegroep P2/n met Z=4 in 'n eenheidsel met dimensies: a = 15.184(1) Å, b = 17.112(1) Å, c = 22.256(2) Å, α = 90 °, β = 99.676(4) °, γ = 90 ° by 100 K. „n Kleinste-kwadrate verfyning het 'n konvensionele R indeks van 0.0750 en Rw = 0.1930 vir 2345 refleksies met I > 2σ(I) gelewer. Die palladiumatoom is in 'n vierkantig-planêre geometrie cis gekoördineerd deur twee fosfor- en twee stikstofatome. Daar is addisioneel twee ongekoördineerde stikstofatome van die diazafluooren-9-oon ligand in die aksiale posisies, wat 'n pseudo oktahedriese geometrie induseer. 'n 50% Wanorde in die pakking van een van die fenielringe sowel as in een van die triflaatanione is waargeneem. Die hoë Rw waarde is 'n gevolg van die feit dat een koolstofatoom van die wanordelik-gepakte asetoonoplosmiddel en die waterstofatome daarvan, nie geplaas kon word nie. cis-[Pd2BpymCl4].DMF kristalliseer in die monokliniese ruimtegroep C2/m met Z = 2 in 'n eenheidsel met dimensies: a = 10.73(7) Å, b = 14.24(8) Å, c = 5.938(2) Å, α = 90 °, β = 108.229(4) °, γ = 90 ° by 100 K. Kleinste-kwadrate verfyning het 'n konvensionele R indeks van 0.032 en Rw = 0.0893 vir 1110 refleksies met I > 2σ(I) gelewer. Die kompleks bestaan uit twee palladiummetaalsenters wat deur die 2,2‟-bipirimidienligand gebrug word. Elke palladiumatoom word deur twee chloridoligande en twee stikstofatome in 'n vierkantig-planêre geometrie gekoördineer. 'n 25 % Wanorde in die pakking van die DMF oplosmiddel is waargeneem. cis-[Pd(PPh3)2(NO3)2].CO(CH3)2 kristalliseer in die monokliniese ruimtegroep C2/c met Z = 4 in 'n eenheidsel met dimensies: a = 40.343(2) Å, b = 9.749(1) Å, c = 19.78(1) Å, α = 90 °, β = 115.514(1) °, γ = 90 ° by 100 K. Kleinste-kwadrate verfyning het 'n konvensionele R indeks van 0.0773 en Rw = 0.1873 vir 8638 refleksies met I > 2σ(I) gelewer. Die kompleks besit 'n vierkantig-planêre geometrie rondom die palladiumatoom, gekoördineer deur twee suurstof- en twee fosforatome in 'n cis oriëntasie. Die hoë Rw waarde is 'n gevolg van die feit dat een koolstofatoom van die wanordelik-gepakte asetoonoplosmiddel en die waterstofatome daarop, nie geplaas kon word nie. Die kompleks cis-[Pd2BpymCl4].DMF se katalitiese aktiwiteit is voorlopig in die Heck koppelingsreaksie en Wacker oksidasieproses geëvalueer, maar geen herhaalbare resultate is as gevolg van infrastruktuur- en tydsbeperkings verkry nie.
Dissertation (M.Sc. (Chemistry))--University of the Free State, 2009
Keywords: Organic compounds; Catalysis; Organometallic compounds; Platinum; Palladium; Metal organic frameworks; Crystal structure; Nanoparticles; Pyrazine; 2,2'-bipyrimidine; 4,4-bipyridine